Participatory communication of Guntung urban village community Bontang city in compost management - Almalita, Restu; Dwivayani, Kadek Dristiana (Manajemen Komunikasi, 2023)
Compost management is one of the efforts to manage organic waste to maintain environmental quality. Communication needs to be done to encourage community participation. The purpose of this study was to describe the participatory communication process applied by the Mekarsari Guntung Sejahtera Cooperative in compost management. This study used a qualitative descriptive approach by utilizing participatory communication theory as an analysis tool, which includes heteroglossia, dialogic, polyphony, and carnival. The data analysis technique used was the Miles, Huberman, and Saldana interactive model data analysis. The study results indicated that the Mekarsari Guntung Sejahtera Cooperative has implemented participatory communication patterns. In heteroglossia, this group has accommodated the involvement of various parties with diverse backgrounds. The involvement of young people was not significant yet, and women dominated the gender proportion. The dialogue showed that this group conducted internal and external dialogue. The dialogue then became a space for cooperatives to discuss programs, evaluate, and share business results. In polyphony, this group gathered opinions on programs implemented by members and the community. The carnival showed that the communication style carried out by this group took place informally. However, media management as information dissemination for increasing participation was not optimal due to low technology adaptation. The Mekarsari Guntung Sejahtera Cooperative needs to increase collaboration with community elements in Guntung Urban Village and evaluate the diversity of media and approaches used to attract more significant participation and the programs implemented to run on sustainable principles.